Pengaruh Penerapan Green Accounting, Struktur Modal, dan Akuntansi Lingkungan Terhadap Kinerja Perusahaan Pada Perusahaan Sektor Pertambangan yang Terdaftar di BEI Tahun 2019-2022 - Nayla Valeska; Sofie Sofie (CV. Ulil Albab Corp, 2024)
This research examines and analyzes the application of green accounting, capital structure and environmental accounting to company performance in mining sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The data analysis technique used in this research is multiple linear analysis and green accounting measurement using the formula for environmental costs divided by net profit. This research uses a quantitative type of research, which emphasizes the analysis of numerical data (numbers) using statistical methods with the SPSS 25 application. The results of this research show that green accounting has no significant effect on company performance, capital structure has no effect, and environmental accounting has an effect on company performance.